On becoming a ' School of Education ' : Our Mission as Educators - Ishumi, Abel G. (Papers in Education and Development, 2018)
The current School of Education changed its name from the Faculty of Education, which it became in 1989. Before that date it had been a Department of Education within a large Faculty of Arts and Social Sciences, tracing its beginning in 1964, along with a few other departments of that Faculty. On formation in 1964, the Faculty of Arts and Social Sciences was second to the very first Faculty of Law, which had been established along with the whole University College Dar es Salaam (UCD) in 1961. UCD became part of the federal University of East Africa (UEA) in 1963, continuing in this relationship until 1970 when it was broken up into three national universities, including the University of Dar es Salaam for Tanzania. The University of Dar es Salaam experienced its first major reorganisation in 2008-09 which saw a number of changes, including a rescinding of the faculty nomenclature and a clustering of these into either ' colleges ' or ' schools ' within a three-tier structure of department ïƒ  college/school/institute ïƒ  university administration. As the year 2009 witnessed the inauguration or launching of the different "new" colleges and schools, it was the turn, on the 16th of May, for the former Faculty of Education to inaugurate and celebrate its new mantle as the School of Education. What follows is a collection of a few thoughts, observations and ideas that were put together by the author in what might be taken as a ' talk ' as the ' Faculty ' was wearing the new cloak of ' School ' .